Effect of probiotic drugs and their metabolites on the microflora of digestive canal of broiler chickens - A. Daskalova; K. Kucheruk; D. Zasekin; J. Hryb (Ukrainian Journal of Veterinary Sciences, 2023)
The relevance of the study is conditioned by the growing demand of the population for safe and organic poultry products. Various microbiological preparations are used as therapeutic and preventive means and alternatives to the use of antibiotics in organic poultry farming. The purpose of the study is to determine the effect of preparations of probiotic microorganisms and their metabolites on the optimal composition of the microflora of the digestive canal, the general condition, and the liveability of broiler chickens. The effect of various types of drugs on broiler chickens was investigated: the probiotic LactoPharm LP12, the postbiotic Bacteriosan, and a bacteriocin nisin solution. The qualitative and quantitative composition of the microflora of the digestive canal of broiler chickens was determined by the method of bacteriological cultures. The disc diffusion method, using commercial discs with a minimum inhibitory concentration, revealed sensitivity to antibiotics. The effective effect of the new postbiotic Bacteriosan on the intestines of poultry was confirmed – no coagulase-positive Staphylococcus aureus was isolated on the 30th day of the experiment, and the lowest titre of Escherichia coli was recorded on days 30, 60, and 81 of the experiment. In terms of the content of lactic acid bacteria in the intestines of broiler chickens, the highest concentration was found in the experimental groups that used the probiotic LactoPharm LP12 and the experimental postbiotic by 21% and 32%, respectively, compared to control group. Treatment of bedding material with prophylactic drugs in poultry houses of experimental groups contributed to air sanitation and a decrease in the microbial background of the room compared to the control. The lowest mortality rate of chickens (-12%) was observed when using probiotics and postbiotics, due to the positive effect on the microbiocenosis of the digestive canal. When using an aqueous solution of nisin, the mortality rate was 14%. Thus, the use of the postbiotic Bacteriosan at a dose of 5 mL/kg of feed and the probiotic LactoPharm LP12 at a dose of 1 g/L of drinking water for seven days with a weekly break during the entire period of poultry rearing was experimentally substantiated, which will allow for effective prevention of infectious diseases and increase the liveability of broiler chickens